Nodal and BMP expression during the transition to pentamery in the sea urchin Heliocidaris erythrogramma: insights into patterning the enigmatic echinoderm body plan. Issue 1 (December 2017) - Koop, Demian; Cisternas, Paula; Morris, Valerie; Strbenac, Dario; Yang, Jean; Wray, Gregory; Byrne, Maria
Abstract Background The molecular mechanisms underlying the development of the unusual echinoderm pentameral body plan and their likeness to mechanisms underlying the development of the bilateral plans of other deuterostomes are of interest in tracing body plan evolution. In this first study of the spatial expression of genes associated with Nodal and BMP2/4 signalling during the transition to pentamery in sea urchins, we investigateHeliocidaris erythrogramma, a species that provides access to the developing adult rudiment within days of fertilization. Results BMP2/4, and the putative downstream genes, Six1/2, Eya, Tbx2/3 andMsx were expressed in the earliest morphological manifestation of pentamery during development, the five hydrocoele lobes. The formation of the vestibular ectoderm, the specialized region overlying the left coelom that forms adult ectoderm, involved the expression of putative Nodal target genesChordin, Gsc andBMP2/ 4 and putative BMP2/4 target genesDlx, Msx andTbx . The expression ofNodal, Lefty andPitx2 in the right ectoderm, andPitx2 in the right coelom, was as previously observed in other sea urchins. Conclusion That genes associated with Nodal and BMP2/4 signalling are expressed in the hydrocoele lobes, indicates that they have a role in the developmental transition to pentamery, contributing to our understanding of how the most unusual body plan in the Bilateria may have evolved. We suggest that the Nodal and BMP2/4 signalling cascades might have been duplicated or split during the evolution to pentamery.